A Contrast Stretching Bilateral Closing Top‐Hat Otsu Threshold Technique for Crack Detection in Images. Issue 2 (9th July 2012) - Sim, K. S.; Kho, Y. Y.; Tso, C. P.; Nia, M. E.; Ting, H. Y.
Summary Detection of cracks from stainless steel pipe images is done using contrast stretching technique. The technique is based on an image filter technique through mathematical morphology that can expose the cracks. The cracks are highlighted and noise removal is done efficiently while still retaining the edges. An automated crack detection system with a camera platform has been successfully implemented. We compare crack extraction in terms of quality measures with those of Otsu's threshold technique and the another technique (Iyer and Sinha, 2005). The algorithm shown is able to achieve good results and perform better than these other techniques. SCANNING 35: 75‐87, 2013. © 2012 Wiley Periodicals, Inc.